2011
DOI: 10.1073/pnas.1101841108
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis inhibitor of macrophage (AIM) is required for obesity-associated recruitment of inflammatory macrophages into adipose tissue

Abstract: Infiltration of inflammatory macrophages into adipose tissues with the progression of obesity triggers insulin resistance and obesity-related metabolic diseases. We recently reported that macrophage-derived apoptosis inhibitor of macrophage (AIM) protein is increased in blood in line with obesity progression and is incorporated into adipocytes, thereby inducing lipolysis in adipose tissue. Here we show that such a response is required for the recruitment of adipose tissue macrophages. In vitro, AIM-dependent l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
95
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 37 publications
0
95
0
3
Order By: Relevance
“…On the other hand, the activation of FAS, together with a decrease in FFAs, was observed in AIM −/− mice. It was reported that the inhibition of FAS activity due to AIM caused lipolysis in adipocytes without the activation of the cAMP/AMPK signaling pathway, hormone‐sensitive lipase, and adipose triglyceride lipase 11. Although it is known that there is an important interaction between AIM and FAS, the FAS activity might be attenuated by negative feedback from the increase in FFAs after MI.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the activation of FAS, together with a decrease in FFAs, was observed in AIM −/− mice. It was reported that the inhibition of FAS activity due to AIM caused lipolysis in adipocytes without the activation of the cAMP/AMPK signaling pathway, hormone‐sensitive lipase, and adipose triglyceride lipase 11. Although it is known that there is an important interaction between AIM and FAS, the FAS activity might be attenuated by negative feedback from the increase in FFAs after MI.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse models and in humans, elevated levels of CD5L occur in conditions with inflammatory components such as LPSinduced fulminant hepatitis 20 , M. tuberculosis infection, 53 obesity, 25 liver cirrhosis, 12,13,62 and allergic asthma, 63 among others. Therefore, in these scenarios, high expression of CD5L may act in an autocrine fashion on MF to modulate inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, this protein is incorporated into adipocytes, thereby modifying adipocyte lipid metabolism and thus resulting in the induction of adipocyte inflammation. 24,25 Interestingly, CD5L incorporation into adipocytes is mediated through scavenger receptor CD36. In fact, CD5L may also be internalized into MK through CD36, suggesting that this scavenger receptor may serve as its cellular receptor for endocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…В гипертрофированных адипоцитах активно происходит липолиз. Образующиеся при этом СЖК, взаимодействуя с TLR-4, индуцируют экспрессию хемокинов, которые приводят к накоплению и активации макрофагов в ЖТ [30,55,56].…”
Section: патогенез воспалительной реакции при ожиренииunclassified
“…В гипертрофированных адипоцитах активно происходит липолиз. Образующиеся при этом СЖК, взаимодействуя с TLR-4, индуцируют экспрессию хемокинов, которые приводят к накоплению и активации макрофагов в ЖТ [30,55,56].При ожирении активированные макрофаги М1-типа (классически активированные) стимулируют лейкоцитарную инфильтрацию на фоне увеличения Th-1-, Th-17-и CD8+-Т-клеток и уменьшения макрофагов M2-типа (альтернативно активированные), Тreg и Th-2 клеток в ЖТ [57][58][59][60]. Учитывая тот факт, что макрофаги способствуют гипертрофии адипоцитов, следует признать, что при ожирении имеет место порочный круг с положительной обратной связью: гипертрофированные адипоциты продуцируют хемокины и их рецепторы, которые инициируют рекрутирование моноцитов/макрофагов в ЖТ.…”
unclassified